2016
DOI: 10.1159/000452271
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome Clustering in the Development of Bovine Binucleate Trophoblast Giant Cells

Abstract: Binucleate trophoblast giant cells (BNC) are the characteristic feature of the ruminant placenta. During their development, BNC pass through 2 acytokinetic mitoses and become binucleate with 2 tetraploid nuclei. In this study, we investigate the number and location of centrosomes in bovine BNC. Centrosomes typically consist of 2 centrioles surrounded by electron-dense pericentriolar material. Duplication of centrosomes is tightly linked to the cell cycle, which ensures that the number of centrosomes remains co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There is a small body of literature specifically related to PGCCs (74 PubMed‐listed entries with query: [PGCCs] vs 3,857,567 with query [cancer]; accessed 10 May 2019; Figure ), but this literature, taken holistically, makes a compelling case for defining them as the essential keystone cancer species and actuators of tumorigenesis, therapeutic resistance, and recurrence in metastatic disease. Keystone species are relatively few in number, but have a significant impact on the health and composition of the ecosystem.…”
mentioning
confidence: 99%
“…There is a small body of literature specifically related to PGCCs (74 PubMed‐listed entries with query: [PGCCs] vs 3,857,567 with query [cancer]; accessed 10 May 2019; Figure ), but this literature, taken holistically, makes a compelling case for defining them as the essential keystone cancer species and actuators of tumorigenesis, therapeutic resistance, and recurrence in metastatic disease. Keystone species are relatively few in number, but have a significant impact on the health and composition of the ecosystem.…”
mentioning
confidence: 99%
“…Furthermore, a truncation mutation in cNap1 in cows is at the origin of centriole splitting and cell migration defects, as well as Seckel-like syndromes ( Floriot et al, 2015 ). Clustering of centrioles may also contribute to the functionality of placental cells and thereby insure early embryonic growth, since specialized cells of the embryonic trophoectoderm, trophoblast giant cells, are polyploid and display centrosome amplification ( Klisch et al, 2017 ; Buss et al, 2022 ), with clustered centrioles identified in binucleate bovine trophoblast cells ( Klisch et al, 2017 ). Thus, early embryonic growth defects in our ninein-deficient mouse embryos may be explained in part by impaired centriole clustering, in addition to potential abnormalities in proliferation and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…These represent different paths towards polyploidy, including endocycling, cell fusion and cell division failure. (Klisch et al, 2017;Sakaue-Sawano et al, 2013;Simmons et al, 2007;Simmons & Cross, 2005;Zybina & Zybina, 2005;Zybina & Zybina, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These represent different paths toward polyploidy, including endocycling, cell fusion, and cell division failure ( Zybina and Zybina, 1996 , 2005 ; Simmons and Cross, 2005 ; Simmons et al ., 2007 ; Sakaue-Sawano et al. , 2013 ; Klisch et al. , 2017 ).…”
Section: Introductionmentioning
confidence: 99%